Sinergi Kader dan Modal Sosial dalam Transformasi Program Kesehatan di Kampung KB Jenawi Desa Mertasinga Kabupaten Cirebon - Khairunissa Aura Fatimah; Fajar Fajar (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
The success of the health program in Kampung Keluarga Berkualitas (KB) Jenawi is hampered by communication gaps and cultural resistance, making the vital role of community health worker as local figures who utilize social capital important in mobilizing community participation and optimizing the program. The purpose of this article is to identify the role of community health worker's social capital in optimizing the health program in Kampung KB Jenawi. This study uses a qualitative approach with observation and informant interview techniques with several criteria, namely community health worker, residents, village midwives, Health Field Officers (PLKB), and the head of the neighborhood association (RW). The data analysis technique used in this study is thematic data analysis. The results of this study show that: (1) the implementation of bonding social capital of community health worker is more evident in the BKB and BKL health programs in the form of collective homogeneity, internal traditions and solidarity, communication patterns, as well as social and psychological support; (2) the actualization of bridging social capital was aimed at the BKB and BKL programs in the form of internal actor collaboration and external community collaboration, (3) and the implementation of linking social capital was carried out in the BKB, BKR, and BKL programs in the form of government agency networks and government agency delegate actors. The conclusion is that the optimization of each health program in Kampung KB Jenawi is supported by the respective social capital of community health worker.